1964
DOI: 10.1111/j.1365-2621.1964.tb01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Aromatic Compounds in Sap Composition of Maple Sap and Sirup

Abstract: SUMMARY The constituents of a chloroform extract of maple sap were resolved by gas chromatography. The high‐boiling components were found to be the aromatic compounds coumarin, vanillin, syringaldehyde, coniferyl aldehyde, and 2, 6‐dimethoxybenzoquinone. None were present in the sap in concentrations greater than 1 ppm. An ether‐insoluble lignin was indicated by both chemical tests and infrared data. No significant differences were observed between the chromatograms of early and late sap extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Many studies have shown that phenolic phytochemicals have high antioxidant activity and other biological properties (Al-Farsi, Alsalvar, Morris, Baron, & Shahidi, 2005;Seeram et al, 2005;Shahidi & Ho, 2005;Yahia, 2010). Various researchers have identified the phenolic constituents of maple syrup in different extracts (Abou-Zaid et al, 2008;Filipie & Underwood, 1964;Kermasha et al, 1995;Li & Seeram, 2010;Potter & Fagerson, 1992) and were further related to antioxidant (Legault et al, 2010;Li & Seeram, 2010;Theriault et al, 2006;Yosikawa, Kawahara, Arihara, & Hashimoto, 2010) human cancer cell antiproliferative (Legault et al, 2010;Theriault et al, 2006) and anti-inflammatory properties (Legault et al, 2010). The present study showed that maple syrup phenolic-enriched extracts have type 2 diabetes management potential, via inhibition of carbohydrate hydrolyzing enzymes, with the MSBuOH fraction having the highest bioactivity.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have shown that phenolic phytochemicals have high antioxidant activity and other biological properties (Al-Farsi, Alsalvar, Morris, Baron, & Shahidi, 2005;Seeram et al, 2005;Shahidi & Ho, 2005;Yahia, 2010). Various researchers have identified the phenolic constituents of maple syrup in different extracts (Abou-Zaid et al, 2008;Filipie & Underwood, 1964;Kermasha et al, 1995;Li & Seeram, 2010;Potter & Fagerson, 1992) and were further related to antioxidant (Legault et al, 2010;Li & Seeram, 2010;Theriault et al, 2006;Yosikawa, Kawahara, Arihara, & Hashimoto, 2010) human cancer cell antiproliferative (Legault et al, 2010;Theriault et al, 2006) and anti-inflammatory properties (Legault et al, 2010). The present study showed that maple syrup phenolic-enriched extracts have type 2 diabetes management potential, via inhibition of carbohydrate hydrolyzing enzymes, with the MSBuOH fraction having the highest bioactivity.…”
Section: 2mentioning
confidence: 98%
“…Maple syrup is produced primarily in North America with the vast majority of the world's supply coming from Canada (85%; primarily Quebec), followed by United States (Perkins & van der Berg, 2009). Previous reports have shown that maple syrup contains a wide variety of phenolic phytochemicals (Abou-Zaid, Nozzolillo, Tonon, Coppens, & Lombardo, 2008;Filipie & Underwood, 1964;Kermasha, Goetghebeur, & Dumont, 1995;Li & Seeram, 2010;Potter & Fagerson, 1992), which may have positive effects on human health. Recently, phenolic-enriched extracts of maple syrup were shown to have antioxidant, anti-mutagenic and human cancer cell anti-proliferative properties (Legault, Girard-Lalancette, Grenon, Dussault, & Pichette, 2010;Li & Seeram, 2010;Theriault, Caillet, Kermasha, & Lacroix, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Among the phytochemicals that have been previously reported from maple syrup, the phenolic class predominates. For example, vanillin, syringaldehyde, coniferaldehyde, and cinnamic acid and benzoic acid derivatives, as well as flavonoids (flavanols and flavonols), have been identified in maple syrup extracts .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a comprehensive investigation of maple syrup phenolics is necessary to evaluate the biological properties and potential human health benefits of this natural sweetener. Previous phytochemical research has been conducted on maple syrup extracts, namely, ethyl acetate, chloroform, dichloromethane, and diethyl ether extracts . Whereas these organic solvents are commonly used for the extraction of phytochemicals from complex food matrices, it is possible that higher polarity solvents, such as n -butanol, may contain previously unreported phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a comprehensive investigation of maple sap phenolics is necessary to evaluate the native components and biological properties of this natural sweetener. Previous phytochemical studies on maple sap were limited to the detection by gas chromatography of coumarin, vanillin, syringaldehyde, coniferyl aldehyde, and 2,6-dimethoxybenzoquinone [5]. Maple saps were passed through an Amberlite XAD, and then eluted subsequently at 20%, 50%, and 100% MeOH.…”
Section: Introductionmentioning
confidence: 99%